IDENTIFICATION OF METABOLITE COMPOUNDS IN EXTRACT AND EXTRACT FRACTIONS OF MORINGA LEAVES (Moringa oleifera) USING THIN LAYER CHROMATOGRAPHY (TLC) METHOD - Khairi, Widayatul; Safwan; Hendriyani, Irmatika (Universitas Airlangga, 2025)
Moringa oleifera, known in Indonesia as